Design and Fabrication of an Electrode for Low-actuation-Voltage Electrowetting-on-Dielectric Devices. (2015) - Samad, M.F.; Kouzani, A.Z.; Rahman, M.M.; Magniez, K.; Kaynak, A.
Abstract: This paper presents the design and fabrication of an electrode for low-actuation-voltage electrowetting-on-dielectric (EWOD) devices. The electrode which takes advantage of a novel shape is used to develop an EWOD device. The fabrication process for the electrode and the device development includes laser exposure, wet developing, etching, and stripping. A dielectric layer of 5% (wt./wt.) Polyvinylidene difluoride (PVDF) is used for the electrode insulation. In addition, a very thin (50 nm) layer of Teflon is coated on the EWOD surface to provide hydrophobicity. It is observed that a thin and high dielectric-constant layer can reduce the actuation voltage in the EWOD device. An actuation voltage of 14.8 V was achieved by the EWOD device.